Enlightening Gliotoxin Biological System in Agriculturally Relevant Trichoderma spp. - Bulgari, Daniela; Fiorini, Lisa; Gianoncelli, Alessandra; Bertuzzi, Michela; Gobbi, Emanuela (Frontiers in Microbiology, 2020)
Gliotoxin (GT) is a dual fungal secondary metabolite (SM). It displays pleiotropic activities; possesses medicinal properties and biocontrol abilities but, unfortunately, has toxic properties in humans. Various Trichoderma species are used as fungal biological control agents (BCAs), as a sustainable alternative for crop protection worldwide. Among them is Trichoderma virens, a GT-producing fungus. Since no information was available on the genetically coded prerequisites for the production of GT in other Trichoderma spp., genome analyses were carried out in 10 Trichoderma spp. genomes. Moreover, a real-time PCR assay set up ad hoc and HPLC analyses were employed to understand the GT producing biological systems in T. virens GV29-8 (TvGV29-8) and T. afroharzianum T6776 (TaT6776), two relevant biocontrol fungi. The structure of the GT biosynthesis genes (GT-BG) is polymorphic with two distinct types associated with the ability to produce GT. GliH, a key protein for GT synthesis, is absent in most of the Trichoderma GT biosynthetic pathways, which may be the reason for their inability to produce GT. The GT-BG are expressed in TvGV29-8 as expected, while they are silent in TaT6776. Interestingly, in the GT-nonproducing TaT6776, only gliA (putative GT transporter) and gtmA (putative GT S-methyltransferase) were induced by exogenous GT, underlining the ability of this strain to reduce the deleterious effect of the toxin. This ability is confirmed by growth assays and by the detection of the bis-thiomethylated form of GT catalyzed by GtmA in the culture medium supplemented with GT. To the best of our knowledge this is the first general description of the GT biological system in different Trichoderma spp. as far as the GT-BG content and organization is concerned and a preliminary insight into their functionality.